تحليل اثر الدين العام في بعض المتغيرات الاقتصادية في دولة مصر  (2011- - دراسة للمدة من ( 2001 - مايح شبيب الشمري; حيدر جواد كاظم (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: إن د ا رسة وتحلیل موضوع الدین العام من جوانبه المختلفة والمتنوعة والمعقدة یساعد في اتخاذ ق ا ر ا رت عقلائیة موحدة على مستوى الاقتصاد المصري، ومحاولة التحكم في المشاكل الناجمة والإلمام بها، و یهدف البحث إلى د ا رسة هیكل الدین العام ومؤش ا رته، والآثار الناجمة عنه في مصر وتحلیل - وتقدیر اثر الدین العام الداخلي والخارجي على بعض المتغی ا رت الاقتصادیة للمدة من( 2001 .(2011 وقد توصلت الد ا رسة الى مجموعة من الاستنتاجات كان أبرزها إن النماذج المقدرة في مصر بینت الأثر الایجابي للدین الداخلي في تعزیز الإنفاق العام وبالتالي ارتفاع مستوى الائتمان المحلي مما انعكس في زیادة معدلات الاستثمار وتحقیق نمو في الناتج بمعدلات مقبولة ،مما یعكس عقلانیة استخدام الدین الداخلي ،أما اثر خدمة الدین الخارجي فكان سلبیا على الصاد ا رت وانعكس بشكل طفیف في ت ا رجع وضع الحساب الجاري مما أدى بدوره لانخفاض معدل الاستی ا ردات في نهایة المطاف ،إلا إن تلك الآثار لم تكن بمستوى الخطورة بسبب مجموعة عوامل أبرزها التحویلات والمساعدات الخارجیة ،لذا یتطلب التركیز على معالجة الآثار السلبیة للدین الخارجي واستثماره بالشكل الذي یرفع من معدلات النمو الاقتصادي. Abstract: The study and analysis of the topic public debt of its various aspects diversified and complex helps in making decisions unified at the level of the Egyptian economy, and try to control the problems caused and familiarity them, and research aims to study structure of public debt and indicators, and the effects of for in Egypt and the analysis of effect of the internal public debt and on external of some economic variables for the period from (2001-2011). The study reached a set of conclusions, most notably The models estimated in Egypt explained the positive impact of internal debt in the promotion of public expenditures and hence the high level of internal credit which reflected in increased rates of investment and growth in output at acceptable rates, reflecting the rational use of internal debt, the effect of external debt service was negatively on exports and reflected a slight decline in the current account position, which in turn led to a lower rate of imports, but that these effects were not the level of dangerous because of a combination of factors notably transfers foreign assistances will require focus on addressing the negative effects of external debt and invested form in which increases the rates of economic growth.